2021
DOI: 10.1002/mnfr.202100100
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Potent Sleep‐Promoting Effect of Turmeric: Turmeric Increases Non‐Rapid Eye Movement Sleep in Mice Via Histamine H1Receptor Blockade

Abstract: Scope: Turmeric has a broad spectrum of biological properties; however, the sleep-promoting effects of turmeric have not yet been reported. Thus, this study aims to investigate the effect of turmeric on sleep and the molecular mechanism underlying this effect. Methods and Results: Pentobarbital-induce sleep test and sleep-wake profile assessment using recorded electroencephalography are used to evaluate the hypnotic effects of the turmeric extract (TE) compared to diazepam on sleep in mice. Additionally, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Sleep architecture was analyzed using the method described by Um et al [ 33 ]. A head mount (Pinnacle Technology, Inc., Lawrence, KS, USA) was chronically implanted in mice under pentobarbital anesthesia (50 mg/kg) to record electroencephalogram (EEG) and electromyogram (EMG) signals.…”
Section: Methodsmentioning
confidence: 99%
“…Sleep architecture was analyzed using the method described by Um et al [ 33 ]. A head mount (Pinnacle Technology, Inc., Lawrence, KS, USA) was chronically implanted in mice under pentobarbital anesthesia (50 mg/kg) to record electroencephalogram (EEG) and electromyogram (EMG) signals.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in the present study, we investigated the constituents involved in the sleep effects of TE based on our previous results. 10 Finally, we demonstrated that curcuminoids, a major component of turmeric, decrease sleep latency and increase NREMS frequency in mice via the inhibition of the H1R.…”
Section: Discussionmentioning
confidence: 85%
“…9 In recent, it has been reported that turmeric extract (TE) exhibits sleep-promoting effects via histamine H1 receptor (H1R) blockade in animal models. 10 Oral administration of TE significantly increased non-rapid eye movement sleep (NREMS) duration and decreased sleep latency in C57BL/6N mice. These hypnotic effects were not observed in H1R knockout (KO) mice.…”
Section: Introductionmentioning
confidence: 98%
“…Notably, activation of GABAA receptor has been associated with sedative, hypnotic and anticonvulsant effects (Choi et al, 2014). Analysis of sodium pentobarbital-induced sleep is one of the most commonly used methods for detection of sleep quality in animals (Um et al, 2021). In this study, we employed this method for analysis of sleep quality in mice, and found that Hp-associated chronic gastritis caused poor sleep quality in mice, especially females.…”
Section: Discussionmentioning
confidence: 94%